2019
DOI: 10.1108/bepam-10-2018-0124
|View full text |Cite
|
Sign up to set email alerts
|

Project-specific constraints influencing productivity of tradespeople in the Nigerian construction industry

Abstract: Purpose The purpose of this paper is to establish the perception of tradespeople about project-specific constraints (PSCs) influencing construction productivity in Nigeria. Design/methodology/approach Using a qualitative descriptive survey comprising face-to-face semi-structured interviews and a purposive sampling method, views of eight groups of tradespeople and seven project managers on live construction projects in Nigeria were collected. The study used conventional content analysis with the aid of NVivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The complaints of fatigue and sleepiness during the day directly correlate to laborers' shift timings. Several studies have shown that shift laborers have higher truancy rates, accidents and errors in construction sites, personal problems, and problems related to construction work ( 21 ). Shift laborers are likelier to report appalling sleep quality, insomnia, and daytime fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…The complaints of fatigue and sleepiness during the day directly correlate to laborers' shift timings. Several studies have shown that shift laborers have higher truancy rates, accidents and errors in construction sites, personal problems, and problems related to construction work ( 21 ). Shift laborers are likelier to report appalling sleep quality, insomnia, and daytime fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…A Cronbach’s alpha reliability test, which was conducted to test for the reliability of the data collection instrument, shows excellent internal consistency, posting a Cronbach’s alpha of 0.942. Cronbach’s α values greater than 0.7 indicate excellent data reliability (Ugulu et al. , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Lack of sleep (less than seven hours) was linked with a higher risk of injury during the National Health Interview Survey (Azhar and Choudhry, 2016). Also, sleep deprivation has been associated with job-related injuries in patients who have suffered serious work injuries (Ugulu et al, 2020;Brick et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of this study, construction tradespeople include craftsmen, artisans, and other site operatives that are different from the built environment professional and experts. Tradespeople are workers with trade specialisations where work experience requires training on the job; due to modernization and to avoid gender bias, it is more fashionable to use the term 'tradespeople' (Ugulu et al, 2019). They include skilled carpenters, masons, plumbers, plasterers, painters, and glaziers.…”
Section: Construction Tradespeople and Accident Exposurementioning
confidence: 99%